Odpowiedzi

Najlepsza Odpowiedź!
2010-03-23T16:38:31+01:00
A) 4c-(3c+2)-10c =4c-3c-2-10c = c-10c-2 = -9c-2
b) 7x-8-(5x+6) = 7x-8-5x-6 = 2x-14
c) 9y-(8-3y)+16 = 9y-8+3y+16 = 12y+8
d) 5x-(2-4x)+8x-7 = 5x-2+4x+8x-7 = 17x-9
e) -(-5c-8)+6-9c-c = 5c+8+6-10c = 14-5c
f) -4(3x-6)-3(2+7x) = -12x+24-6-21x = 18-33x
g) 5(3z-7)-9(-8z-6) = 15z-35+72z+54 = 87z+19
h) -3(5x-4)+8(-3x+2) = -15x+12-24x+16 = 28-39x
i) 7x-3(5x+2)-6(7+2x) = 7x-15x-6-42-12x = -20x-48
j) -5(3y-7)-2(6+4y)+3y = -15y+35-12-8y+3y = 23-20y
1 5 1
2010-03-23T16:40:24+01:00
A)4c-3c-2-10c=-9c-2
b)7x-8-5x-6=2x-14
c)9y-8+3y+16=12y+8
d)5x-2+4x+8x-7+17x-9
e)5c+8+6-10c=-5c+14
f)-12x+24-6-21x=-33x+18
g)15z-35+72z+54=87z+19
h)-15x+12-24x+16=-39x+28
i)7x-15x-6-42-12x=-20x-48
j)-15y+35-12-8y+3y=-20y+23
1 5 1